Induced Expression of kir6.2 in A1 Astrocytes Propagates Inflammatory Neurodegeneration via Drp1-dependent Mitochondrial Fission - Song, Nanshan; Zhu, Hong; Xu, Rong; Liu, Jiaqi; Fang, Yinquan; Zhang, Jing; Ding, Jianhua; Hu, Gang; Lu, Ming (Frontiers in Pharmacology, 2021)
Glia-mediated inflammatory processes are critical for Parkinson’s disease (PD) pathogenesis. As the most abundant cells of the brain and active participants in neuroinflammatory responses, astrocytes propagate inflammatory signals and amplify neuronal loss to a greater extent. Hence, intensive control of astrocytic activaton is urgent for the prevention of neurodegeneration. Here we report that the astrocytic kir6.2, as a abnormal response after inflammatory stimuli, promotes neurotoxic reactivity of astrocytes namely A1 astrocytes and thus mediates dopaminergic neuron demise. Using kir6.2 knockout (KO) mice, we find reversal effects of kir6.2 deficiency on A1-like astrocyte activation and neuron loss in lipopolysaccharide (LPS)-induced PD mice model. Further in vitro experiments show that aberrant expression of kir6.2 induced by inflammatory irritants in astrocytes mediates the dynamin-related protein 1 (Drp1)-dependent excessive mitochondrial fragments and results in mitochondrial malfunctions. By deleting kir6.2, activation of astrocytes is reduced and astrocytes-derived neuronal injury is prevented. We therefore conclude that astrocytic kir6.2 may be a promosing target for the understanding of PD pathology and development of PD therapeutics.